The Management of Improving The Quality of Academic Services For Students at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Hasibuan, Mulkan; Fachruddin, Fachruddin; Sit, Masganti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
IAIN Padangsidimpuan switched to UIN with the letter of the Minister of Religion B-379/MA/OT.00/082021 this was to improve the quality of student academic services. Based on this, this study analyzes the Quality Improvement Management of Student Academic Services. The purpose of this study was to analyze the improvement in the quality of academic services for UIN Padangsdimpuan students. In this study, the authors used a qualitative research approach to Ethnographic Research. Methods of collecting data observation interviews and documentation. Planning for Improving the quality of academic services for UIN Padangsidimpuan students in the 2020-2024 RIP, the program for improving the quality of student academic services is the optimization of digitalization-based student academic services. Organizing the field of digitization or digitalization-based student academic services is entrusted by the Vice Chancellor 1 (academic and institutional fields) assisted by the AAKK Bureau (Academic Administration, Student Affairs and Cooperation). Chancellor of IAIN Padangsidimpuan Number 656 of 2019 concerning SOPs for administrative processes or digital-based academic services. Evaluation of improving the quality of digital-based academic service constraints in other faculties has not been effective.